2018
DOI: 10.1128/iai.00009-18
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mycobacterial Ribosomal Proteins as Targets for CD4+T Cells That Enhance Protective Immunity in Tuberculosis

Abstract: remains a threat to global health, and a more efficacious vaccine is needed to prevent disease caused by We previously reported that the mycobacterial ribosome is a major target of CD4 T cells in mice immunized with a genetically modified strain (IKEPLUS) but not in mice immunized with BCG. Two specific ribosomal proteins, RplJ and RpsA, were identified as cross-reactive targets of , but the breadth of the CD4 T cell response to ribosomes was not determined. In the present study, a library of ribosomal protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Subsequent studies described the first, to the best of our knowledge, true genome-wide screen for CD4 T cell epitopes ( 5 ). Subsequent studies report that CD4 T cells can recognize and target epitopes derived from mycobacterial ribosomal proteins and provide protective functions ( 6 , 7 ).…”
Section: Epitope Identification For Mycobacteriamentioning
confidence: 99%
“…Subsequent studies described the first, to the best of our knowledge, true genome-wide screen for CD4 T cell epitopes ( 5 ). Subsequent studies report that CD4 T cells can recognize and target epitopes derived from mycobacterial ribosomal proteins and provide protective functions ( 6 , 7 ).…”
Section: Epitope Identification For Mycobacteriamentioning
confidence: 99%
“…We observed that the transcripts of ribosomal proteins of both smaller and larger subunits of ribosome were upregulated in the Δ higB 1 mutant strain. Studies have shown that these ribosomal proteins are able to elicit a strong CD4 + immune response that might be associated with the faster clearance of the mutant strain in host tissues ( Johnson et al, 2017 ; Kennedy et al, 2018 ). In addition to this, expression level of higA 1 (Rv1956), an adjacent gene of higB 1 toxin was also reduced in the Δ higB 1 deletion strain.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of strong multifunctional Th1 CD4 T cell responses and reduction of lung pathology and bacterial burdens was noted in RplJ-boosted mice after Mtb challenge (11).…”
Section: Introductionmentioning
confidence: 95%
“…In a complementary approach, we generated major histocompatibility complex (MHC) class II-restricted T cell hybridomas from IKEPLUS-vaccinated mice and demonstrated that the CD4LJT cell response recognized several components of the mycobacterial ribosome and was localized in the lungs after Mtb challenge. We then extended our investigations by broadly screening all structural proteins of the Mtb ribosome for their ability to be targeted by CD4 T cells in IKEPLUS immunized mice and showed that the mycobacterial ribosome was highly immunogenic (11). Induction of strong multifunctional Th1 CD4 T cell responses and reduction of lung pathology and bacterial burdens was noted in RplJ-boosted mice after Mtb challenge (11).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation